Analisa Efisiensi Water Tube Boiler Berbahan Bakar Fiber dan Cangkang di Palm Oil Mill Kapasitas 60 Ton TBS/Jam dengan Menggunakan Chemicalogic Steamtab Companion Version 2.0 - Khaidir Maulana; Lukman Lukman; Faqih Burhan Uddin; Ari Susandy Sanjaya (CHEMICA: Jurnal Teknik Kimia, 2016)
Some of the factors that occupy the efficiency of the boiler are superheater pressure, feed water temperature, steam temperature, the amount of steam produced, the amount of fuel consumption, and the calorific value of fuel combustion. ChemicaLogic Steamtab Companion Software is software that use to calculate enthalpy value. The purpose of this research is to get the relationship of variation of superheater pressure with boiler efficiency, variation of feed water temperature with boiler efficiency, variation of steam generated with boiler efficiency, analyzing fuel calorific value of 75% fiber + 25% shell and analyzing water tube boiler. From the analysis result that has been done, the relation of variation of superheater pressure with boiler efficiency is not constant but irregular or up and down, the relation of feed water temperature variation with boiler efficiency is not constant but irregular or up and down, the relation of variation of steam produced with boiler efficiency relatively up. The highest burning calorific value (HHV) is 21078,4853 kJ/kg. The lowest burning calorific value (LHV) is 17838,4853 kJ/kg, the highest boiler efficiency value generated is 54.7% and the lowest boiler efficiency amounting to 44.23%.